MANDIBULAR THIRD MOLARS IN THE SIGMOID NOTCH: A RARE STUDY AND CLINICAL MANAGEMENT - Javanshir Asadov; Tuğba Kuşlu; Begüm Genç; Sırmahan Çakarer; Sabri Cemil İşler (Sabiad)
Ectopic mandibular third molars (EMTMs) are uncommon, especially in atypical locations like the sigmoid notch. Their aetiology includes developmental anomalies, pathological conditions,trauma, and iatrogenic factors. EMTMs are uncommon and frequently asymptomatic, typically identified during routine radiographic examinations. Often associated with pathologies such as cysts and inflammation, EMTMs predominantly affect females after the fourth decade of life. This case report presents a 49-year-old male patient who presented with symptoms of swelling, limited mouth opening, and infection, attributed to an EMTM in the sigmoid notch associated with a dentigerous cyst. Radiological imaging revealed the precise location and extent of the EMTM and cyst. The choice of surgical approach, based on 3D imaging, should minimise risks and optimise outcomes. Surgical management involved an intraoral approach for extraction of the impacted tooth and enucleation of the cyst, leading to the resolution of symptoms and restoration of normal mouth opening. Literature review emphasises the significance of accurate diagnosis through advanced imaging techniques and tailored surgical strategies for the effective management of EMTMs.